The Differences of Saliva pH between Consumption of Sucrose Chocolate and Stevia Chocolate in 10-12 years Old Children - Widianto, Shafwan Rafif; Kaswindiarti, Septriyani; Sari, Nendika Dyah Ayu Murika; Faizah, Ariyani (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Children enjoy eating sweet treats like chocolate, which often contains sugar as a sweetener. This can influence the pH of saliva and affect the processes of demineralization and remineralization in teeth. Up until now, there has not been any research on the variation in saliva pH when consuming regular chocolate (with sucrose) compared to chocolate sweetened with stevia in children aged 10-12 years. This study aims to explore the differences in saliva pH between children in this age group who consume sucrose chocolate and those who consume stevia chocolate. Methods: In this study, a Quasi-Experimental design was employed, and approval was granted by the Ethical Committee of Health Research at Dr. Moewardi General Hospital under Ethical Clearance Number 2.045/XI/HREC/2023. Initially, twenty-one children aged 10-12 years from SD Muhammadiyah 1 Surakarta had their saliva measured before any intervention. They were then given chocolate containing 30% sucrose for 60 seconds. Ten minutes after this intervention, the children were asked to collect saliva in their mouths and spit out 2ml into a sterile container. The collected saliva was then tested for pH using a pH metre (Hanna brand, Romania). On the following day, the subjects were instructed to consume chocolate sweetened with 1% stevia using the same method. The average difference in saliva pH before and two days after the intervention was analysed using an independent T-Test on the saliva pH difference. Results: The research discovered that the average change in saliva pH before and after eating sucrose chocolate was 0.3413 ± 0.12557, while for stevia chocolate, it was 0.1444 ± 0.07698. Tests for normal distribution (Shapiro-wilk test) and data homogeneity (Levene’s homogeneity test) both indicated acceptable conditions (p>0.05). The independent T-Test revealed significant differences in saliva pH between children aged 10-12 years when consuming sucrose chocolate compared to stevia chocolate (p<0.05). Conclusion: In summary, the study on saliva pH differences in 10-12-year-old children after eating sucrose chocolate compared to stevia chocolate indicates that there is indeed a distinction in saliva pH between the two. Children who consumed sucrose chocolate showed a lower saliva pH compared to those who consumed stevia chocolate.